MiR-135a inhibits malignant proliferation and diffusion of non-small cell lung cancer cells by down-regulating ROCK1 protein. Issue 6 (15th June 2020) - Zhao, Yanan; Sun, Xiaosong; Zhu, Kun; Cheng, Min
Abstract: Objective: To seek the clinical significance and regulatory mechanism of miR-135a and Rho-associated protein kinase 1 (ROCK1) in non-small cell lung cancer (NSCLC). Methods: NSCLC cells were purchased, and miR-135a-mimics, miR-135a-inhibitor, miR-NC, si-ROCK1 and Sh-ROCK1 were transfected into NSCLC cells HCC827 and NCI-H524. qRT-PCR and Western blot were used to detect the expression of miR-135a, ROCK1, Bax, Caspase3, Bcl-2, N-cadherin, vimentin and E-cadherin. MTT, scratch test, Transwell and flow cytometry were used to analyze the cell proliferation, migration, invasion and apoptosis. Results: miR-135a was low expressed in serum of NSCLC group, while ROCK1 was opposite. miR-135a low level or ROCK1 high level was associated with poor prognosis of NSCLC and lower 3-year OS. Over-expression of miR-135a and inhibition of ROCK1 expression could control malignant growth and diffusion of cells and expression of Bcl-2, N-cadherin and vimentin proteins, and promote apoptosis and expression of Bax, Caspase3 and E-cadherin proteins. After transfection of miR-135a-mimics+sh-ROCK1 to HCC827 and NCI-H524, the malignant proliferation and diffusion behavior of the cells were not different from those of the miR-NC group with no transfection sequence. The double luciferase report revealed that miR-135a has a targeting relationship with ROCK1. Conclusion: miR-135a is abnormally down-regulated in NSCLC. As a serum indicator, miR-135a has the potential to diagnose NSCLC and predict prognosis. The up-regulated expression of miR-135a protein can down-regulate the ROCK1 protein, inhibit the malignant proliferation, migration, invasion, EMT and other diffusion behaviors of NSCLC cells, and increase the apoptosis ability of cells.